A New Water‐Soluble Phosphorus‐Dipyrromethene and Phosphorus‐Azadipyrromethene Dye: PODIPY/aza‐PODIPY. Issue 16 (4th March 2015) - Jiang, Xin‐Dong; Zhao, Jiuli; Xi, Dongmei; Yu, Haifeng; Guan, Jian; Li, Shuang; Sun, Chang‐Liang; Xiao, Lin‐Jiu
Abstract PODIPY and aza‐PODIPY have been successfully prepared by the treatment of dipyrromethene and azadipyrromethene with POCl3 in the presence of Et3N. The new PODIPY and aza‐PODIPY dyes are found to have photophysical properties. PODIPY and aza‐PODIPY are water‐soluble, and aza‐PODIPY is suited for labeling living Hep‐2 cells for imaging assays in the near‐infrared region. Molecular orbital calculations show that the increase in the HOMO–LUMO band gap for the lowest energy absorption bands is observed in the new phosphorus‐containing aza‐PODIPY, and the HOMO and LUMO energies of aza‐PODIPY are found to be higher than those of aza‐BODIPY.